Model Alur Pelayanan Pemeriksaan Radiologi Era Pandemi Covid-19 di Rumah Sakit Mayapada Jakarta Selatan - Ziko Pratama; Sri Rahayu (JUDICIOUS, 2021)
In early 2020, the world was shocked by the discovery of a mysterious pneumonia case in Wuhan, Hubei Province, China. As of February 11, 2020, WHO named this disease as Coronavirus Disease 2019 (Covid-19) and it was declared a pandemic on March 11, 2020. This disease is caused by Server Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) a new type of Coronavirus that has never been previously identified in humans. This situation is affected by various aspects of health, including the aspect of health development, namely the delay in the implementation of health services in Indonesia. The purpose of this study was to identify the flow of radiology examination services during the Covid-19 protocol at Mayapada Hospital, South Jakarta. The design of this research is descriptive qualitative with a document review approach in the form of swab results and uses a CT-Scan 128 Slice. The research subjects were adult female patients who underwent a 128 Slice CT-Scan examination at Mayapada Hospital in March 2021. The data collected was in the form of CT-Scan results in cases of positive Covid-19 patients. The results of this study show that the CT-Scan of the thorax is quite clear and can identify the flow of radiological examination services in the Covid-19 protocol at Mayapada Hospital, South Jakarta.